On Gauge Invariant Regularization of Fermion Currents - Gamboa Saraví, Ricardo Enrique (2000)
We compare Schwinger and complex powers methods to construct regularized fermion currents. We show that, although both of them are gauge invariant, they are not always yield the same result.